Hydrodynamic optimisation and thermodynamic scaling fidelity of single and dual-chamber OWC wave energy converters in regular waves - Gunay Gazaloglu; Hasan Gokhan Guler; John Ashlin Samuel; Keri Collins; David Simmonds (Coastal Engineering, 2027)

Wave overtopping on eco-engineered seawalls: Does biodiversity enhancement conflict with coastal protection? - Franz Bauer; Antony M. Knights; Louise B. Firth; John N. Griffin; Andy Foggo; Austin Brown; Martyn Hann; David Simmonds; Mick E. Hanley (Journal of Environmental Management, 2026)

Temporal Variability in Call Rates of Weddell ( Leptonychotes weddellii ) and Leopard ( Hydrurga leptonyx ) Seals Near Davis Station, East Antarctica - Emma A. Simmonds; John M. Terhune; Brian S. Miller; John van den Hoff (Marine Mammal Science, 2026)
We investigated Weddell seal ( Leptonychotes weddellii ) and leopard seal ( Hydrurga leptonyx ) vocalizations using passive acoustic monitoring beneath landfast ice and open water, 5.6 km seaward from Davis Station, East Antarctica. Eight‐minute recordings were manually sampled at 1 h intervals over 24 h every 10 days from 24 July 2021 to 30 January 2022. Call counts for Weddell seals were highest in the winter, lower during the breeding season, and almost absent in the summer. This change coincided with the occurrence of open water over the recording site, a progressive shift in Weddell seal behavior from foraging to aggregating in local fjords for the annual pupping, mating, and molting periods, and an increase in leopard seal—a potential predator—call detection rates. Leopard seal calls were primarily detected in December after the landfast ice broke up. In winter, Weddell seal calling counts were highest at dusk and night, and lowest during the day when the seals may have been feeding. Neither species exhibited a diel calling pattern once there were 24 h of sunlight. Seal locations were associated with the presence and absence of landfast ice, and call detections were influenced by their distances to the recorder.

Half of the habitat of Australia's highly imperilled narrow-range species is outside protected areas - Michelle Ward; Martine Maron; Jeremy S. Simmonds; Mark Lintermans; Nick S. Whiterod; David G. Chapple; Hugh P. Possingham; Sarah M. Legge; Rachael V. Gallagher; Brendan A. Wintle; Samantha Vine; Kita Ashman; et al. (Biological Conservation, 2025)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

A Mediterranean cold front identification scheme combining wind and thermal criteria - Evangelia Bitsa; Helena A. Flocas; John Kouroutzoglou; George Galanis; Maria Hatzaki; George Latsas; Irina Rudeva; Ian Simmonds (International Journal of Climatology, 2021)
The goal of this study is to advance an automated and objective scheme for the identification of cold fronts over the Mediterranean based on wind‐related criteria, MedFTS, by further incorporating thermal criteria, in order to improve the identification of cold fronts on a climatological basis. These thermal criteria are related to cold advection and the thermal front parameter, and their individual or combined contribution is systematically investigated considering different threshold values. For each combination of thermal criteria and/or threshold values, the results are validated with the aid of statistical indices and metrics, and the optimum scheme configuration for the identification of Mediterranean fronts is selected. The advanced version of MedFTS, named MedFTS_DT, having incorporated both dynamic and thermodynamic criteria, is applied and validated for a decade of fronts over the Mediterranean. It was found that the number of erroneously identified cold fronts over Greece was significantly reduced from MedFTS to MedFTS_DT version by almost 40%, as indicated by the statistical metrics. Therefore, the performance of MedFTS_DT is verified to be superior to MedFTS. As a further attempt to investigate the ability of MedFTS_DT to perform adequate climatological analysis in the Mediterranean, the frequency of the cold fronts was calculated over Greece during the period 2007–2016 on a monthly and seasonal basis, demonstrating that the scheme can capture the intra‐annual variations. Finally, the contribution of the cold fronts to the precipitation over the Mediterranean for the same period was investigated, further supporting the scheme's performance.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Taxonomy of the order Mononegavirales: update 2019 - Gaya K. Amarasinghe; María A. Ayllón; Yīmíng Bào; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Camila Chabi-Jesus; et al. (Archives of Virology, 2019)

Taxonomy of the order Mononegavirales: second update 2018 - Piet Maes; Gaya K. Amarasinghe; María A. Ayllón; Christopher F. Basler; Sina Bavari; Kim R. Blasdell; Thomas Briese; Paul A. Brown; Alexander Bukreyev; Anne Balkema-Buschmann; Ursula J. Buchholz; Kartik Chandran; et al. (Archives of Virology, 2019)

On the vertical structure of Mediterranean explosive cyclones - John Kouroutzoglou; Helena A. Flocas; Kevin Keay; Ian Simmonds; Maria Hatzaki (Theoretical and Applied Climatology, 2012)

Location of genes for common bunt resistance in the European winter wheat cv. Trintella - Veronika Dumalasová; James Simmonds; Pavel Bartoš; John Snape (Euphytica, 2012)

Assessing characteristics of Mediterranean explosive cyclones for different data resolution - John Kouroutzoglou; Helena A. Flocas; Ian Simmonds; Kevin Keay; Maria Hatzaki (Theoretical and Applied Climatology, 2011)

Meta-QTL analysis of the genetic control of ear emergence in elite European winter wheat germplasm - Simon Griffiths; James Simmonds; Michelle Leverington; Yingkun Wang; Lesley Fish; Liz Sayers; Leodie Alibert; Simon Orford; Luzie Wingen; Laurence Herry; Sebastien Faure; David Laurie; et al. (Theoretical and Applied Genetics, 2009)

Genetic mapping of a new flowering time gene on chromosome 3B of wheat - Kateřina Pánková; Zbyněk Milec; James Simmonds; Michelle Leverington-Waite; Lesley Fish; John W. Snape (Euphytica, 2008)

Bioactivity and chemistry of the genus Hortonia - Rukmal Ratnayake; B.M. Ratnayake Bandara; Siril Wijesundara; John K. Macleod; Peta Simmonds; Veranja Karunaratne (Natural Product Research, 2008)

pORE: a modular binary vector series suited for both monocot and dicot plant transformation - Catherine Coutu; James Brandle; Dan Brown; Kirk Brown; Brian Miki; John Simmonds; Dwayne D. Hegedus (Transgenic Research, 2007)

Dissecting gene × environmental effects on wheat yields via QTL and physiological analysis - John. W. Snape; M. John Foulkes; James Simmonds; Michelle Leverington; Lesley J Fish; Yingkun Wang; Matteo Ciavarrella (Euphytica, 2007)

Cytochrome f from the Antarctic psychrophile, Chlamydomonas raudensis UWO 241: structure, sequence, and complementation in the mesophile, Chlamydomonas reinhardtii - Loreta Gudynaite-Savitch; Michael Gretes; Rachael M. Morgan-Kiss; Leonid V. Savitch; John Simmonds; Susanne E. Kohalmi; Norman P. A. Hüner (Molecular Genetics and Genomics, 2006)

Genetic basis of inosine triphosphate pyrophosphohydrolase deficiency - Satoshi Sumi; Anthony Marinaki; Monica Arenas; Lynette Fairbanks; Monsor Shobowale-Bakre; David Rees; Swee Thein; Azhar Ansari; Jeremy Sanderson; Ronney De Abreu; Anne Simmonds; John Duley (Human Genetics, 2002)

Developmental and environmental regulation of anthocyanin pigmentation in wheat tissues transformed with anthocyanin regulatory genes - Harvinder S. Chawla; Leslie A. Cass; John A. Simmonds (In Vitro Cellular & Developmental Biology - Plant, 1999)